Japan as a global military power : new capabilities, alliance integration, bilateralism-plus - Hughes, Christopher W. (Elements in politics and society in East Asia, 2022)
"Japan is emerging as a more prominent global and regional military power, defying traditional categorisations of a minimalist contribution to the US-Japan alliance, maintaining anti-militarism, seeking an internationalist role, or carving out more strategic autonomy. Instead, this Element argues that Japan has fundamentally shifted its military posture over the last three decades and traversed into a new categorisation of a more capable military power and integrated US ally. This results from Japan's recognition of its fundamentally changing strategic environment that requires a new grand strategy and military doctrines. The shift is traced across the national security strategy components of Japan Self-Defence Forces' capabilities, US-Japan alliance integration, and international security cooperation. The Element argues that all these components are subordinated inevitably to the objectives of homeland security and re-strengthening the US-Japan alliance, and thus Japan's development as international security partner outside the ambit of the bilateral alliance remains stunted. This title is also available as Open Access on Cambridge Core"--